Paleontological rescue, depositional environment, and stratigraphic correlation of a section of the Ponta Grossa Formation (Paraná Basin) (Terr@ Plural, 2021)
The urban area of Ponta Grossa (PR) occurs on one of the most abundant fossiliferous fields in the country, which records an endemic fauna that occurred in the Devonian of the Paraná Basin. The growing urbanization of the city increasingly buries these outcrops, and new works must be accompanied by a specialized team to safeguard the paleontological heritage. This is the case of the Bosque Mistral project, which exposed many layers of the Ponta Grossa Formation, rich in fossils and trace fossils. This study reports the main fossiliferous occurrences in the section, correlates the section with classical outcrops from the literature, and interprets the main depositional environments as well stratigraphic cycles using an integrated analysis of sedimentology and ichnology. The ichnological distribution also evidences the retrogradation pattern, and, particularly, the occurrence of ichnofabrics dominated by Zoophycos at the top of the section is a signature of high-frequency cycles associated with the transgressive systems tract. Macrofossill biodiversity varies according to the facies, in the sandy and silty layers different organisms from the muddy layers occur. In the former, the epibiont fauna (mainly trilobites and brachiopods) is predominant while in the muddy layers the predominance is the endobiont and semi-endobiont fauna (bivalve mollusks and infaunal brachiopods). In other words, the distribution of taxa across the layers is not random.
Keywords: Devonian; Malvinokaffric Realm; Cruziana ichnofácies; Zoophycos; Geoconservation